Bispecific antibodies targeting BCMA or GPRC5D are highly effective in relapsed myeloma after CAR T-cell therapy - Merz, Maximilian; Dima, Danai; Hashmi, Hamza; Ahmed, Nausheen; Stölzel, Friedrich; Holderried, Tobias A.W.; Fenk, Roland; Müller, Fabian; Tovar, Natalia; Oliver-Cáldes, Aina; Rathje, Kristin; Davis, James A.; et al. (Blood Cancer Journal, 2024)
Despite the astonishing outcomes after chimeric antigen receptor (CAR) T-cell therapy for relapsed refractory multiple myeloma (RRMM), most patients eventually relapse. There are only limited data available on salvage therapies following relapse after BCMA-directed CAR T-cell therapy. Here, we analyzed outcomes of post-CAR T-cell therapy relapse and impact of different salvage strategies in an international cohort of 139 patients (n = 130 ide-cel, n = 9 cilta-cel), receiving talquetamab (n = 28), teclistamab (n = 37), combinations of immunomodulating drugs (IMiDs), proteasome inhibitors (PIs) or CD38 monoclonal antibodies (n = 43), and others (n = 31). The median time to relapse after CAR T-cell therapy was 5 months, 53% had the extramedullary disease (EMD) at relapse, associated with dismal post-relapse outcome (P = 0.005). Overall response and complete response upon salvage therapies were 79% and 39% for talquetamab, 64% and 32% for teclistamab, 30% and 0% for IMiDs/PIs/CD38, and 26% and 3% for others (P < 0.001). Duration of response, as well as median survival, was significantly improved with bispecific antibodies (P < 0.001, respectively). Bispecific antibodies seemed to overcome the poor prognosis associated with early relapse and EMD, and were independent predictors for improved survival in multivariable analysis. In summary, these results suggest bispecific antibodies as the standard of care for relapse after CAR T-cell therapy for RRMM.
CRIS-Team Scopus Importer:2025-02-04